Inhimillinen ja tehokas sosiaali- ja terveysjohtaminen - Syväjärvi, Antti; Pietiläinen, Ville (Tampere University Press, 2016)
The book called "Inhimillinen ja tehokas sosiaali- ja terveysjohtaminen"(Humane and effective social- and health management) gathers together vital debate on social and health management and its needs both in current and future organisations. The perspectives presented in the book are networks, structures, interaction, professional expertise, couture of knowledge, meaningfulness of work, competence, diversity and experience. The book is edited by Antti Syväjärvi and Ville Pietiläinen.